Pendampingan Desa Siaga Bencana Berbasis Komunitas Dalam Meningkatkan Masyarakat Tangguh Bencana Di Desa Dangiang Kecamatan Kayangan Kabupaten Lombok Utara - Yudhi Lestanata; Hidayatullah Hidayatullah; Inka Nusamuda Pratama (JURNAL ABDI MASYARAKAT ILMU PEMERINTAHAN (JAMIN), 2022)
This article is the result of community service activities in the form of community-based disaster preparedness village assistance in improving disaster-resilient communities in Dangiang Village, Kayangan District, North Lombok Regency. Dangiang Village is prone to potential disasters. So to anticipate and deal with disasters so that threats do not cause a protracted burden of suffering, namely by our willingness to prepare for disaster management in a measured, integrated, focused manner, together by reducing the impact of disasters by developing management efforts based on resilient rural communities. Thus, the existence of the village with its community becomes very important. Therefore, this disaster management training and assistance activity provides materials related to: (1) assistance in preparing the PB draft; (2) community-based disaster risk reduction; (3) the importance of PB planning regulations and documents; (4) Assistance in Disaster Potential Inventory. For training activities, the materials prepared according to the needs of the Dangiang Village disaster preparedness volunteer team, include: (1) Emergency First Aid Training (PPGD); (2) Training for the Evacuation of Affected Victims (Lifting Moving); (3) Determination of Evacuation Paths and Temporary Evacuation Places; (4) Simulation of Disaster Emergency and Victim Evacuation.